Nurses’ Awareness of Key Pregnancy Danger Signs and Management Strategies - Sabty, Haila Malik (Jurnal Kebidanan Midwiferia, 2024)
Maternal mortality remains a critical global health challenge, necessitating enhanced awareness of pregnancy danger signs among healthcare providers. Nurses, as primary healthcare providers, play a pivotal role in managing obstetric emergencies; thus, their preparedness is essential for improving maternal outcomes. Despite the significance of their role, there is limited understanding of nurses' knowledge regarding the management of danger signs during pregnancy, particularly in the Al-Basrah region. This study aimed to evaluate nurses' knowledge about managing pregnancy danger signs and explore correlations with demographic factors. Conducted at Al-Basrah Maternity and Children Hospital from December 31, 2023, to March 24, 2024, the study included 50 nurses. Findings revealed that nurses exhibited moderate knowledge (68%) about danger sign management, with significant correlations identified between knowledge and demographic factors such as age, education, and years of experience. However, residency showed no statistical significance. This research highlights specific deficiencies in nurses' knowledge regarding critical pregnancy complications and underscores the need for targeted educational interventions. The study suggests implementing comprehensive training programs to improve nurses' capabilities in recognizing and managing pregnancy danger signs, ultimately contributing to better maternal health outcomes in the region.